PENTINGNYA KUALITAS INFORMASI INTERNAL TERHADAP PENGHINDARAN PAJAK - Heranantio Anggoro Putra; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the influence of Internal Information Quality of an enterprise on tax avoidance planning and tax risk reduction on an enterprise. The population in this study consists of mining companies listed in Indonesia Stock Exchange in 2011-2014 period. Method of collecting data in this research is purposive sampling. After doing sampling stage and data tabulation, achieved 18 companies for 4 years of financial statement period that eligible for the further observation. Hypothesis examinations are using multiple regression analyze and regression analyze usingModerated Regression Analysis (MRA) for the moderating variable on SPSS20.The empirical result of this study shows that Internal Information Quality isn’t influencing tax avoidance. Even it was moderated by improved coordination and reduced uncertainty variables. But, this study shows that higher Internal Information Quality influencing the lower taxk risk